Gingival crevicular fluid interleukin-1 b, prostaglandin E2 and periodontal status in a community population - Y. Zhong (Blackwell Synergy, 2007)
Aim: Interleukin-1 b (IL-1b) and prostaglandin E2 (PGE2) are key inflammatory mediators involved in periodontal disease. The purposes of this molecular crosssectional epidemiological study were to investigate relationships in a community sample between mean concentrations of IL-1b and PGE2 in gingival crevicular fluid (GCF) and (1) clinical periodontal signs and (2) risk factors of host inflammatory response and/or periodontal disease. Material and Methods: The sample comprised 6277 community-dwelling adults aged 52–74 years enrolled in the Atherosclerosis Risk in Communities (ARIC) study. IL-1b and PGE2 concentrations were measured using enzyme-linked immunosorbent assay. Person-level summary variables were computed for maximum pocket depth (MaxPD), maximum clinical attachment level (MaxCAL) and presence/absence of bleeding on probing (BOP). Mean GCF IL-1b and PGE2 concentrations were dependent variables in multiple linear regression models with periodontal measures and covariates as explanatory variables. Results: Both GCF IL-1b and PGE2 were positively related to MaxPD and BOP in multiple regression models (po0.01). Increased levels of IL-1b and PGE2 were associated with body mass index X30 kg/m2. Conclusion: Higher levels of GCF IL-1b and PGE2 were significantly associated with clinical signs of periodontal disease and independently related to patient-based anthropomorphic measures, behaviours and exposures in community-dwelling adults.